Analysis Of The Relationship Between Business Ethics and Sustainability in Companies Working In The Public Sector: A Systematic Literature Review - Esvanti, Mirza; Soetjipto, Budi Eko (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the relationship between business ethics and sustainability business in companies that establish partnerships with the public sector through a Systematic Literature Review (SLR) approach. The background of this study is based on the increasing pressure on companies to not only pursue economic profit, but also pay attention to social and environmental responsibility, especially in the context of collaboration with government agencies. This study examines 16 scientific articles published between 2020 and 2025, obtained from the Scopus database. The analysis shows that the application of business ethics principles such as transparency, accountability, fairness and integrity has a positive correlation with the success of sustainability initiatives. Collaboration with the public sector reinforces the urgency of implementing ethics, given the demands of regulatory compliance and higher social expectations. In addition, business ethics serves as a foundation for building trust between parties, which is key to long-term sustainability. This study recommends the systematic integration of ethics into business strategy, as well as the need for public policies that encourage sustainable business practices through ethical and responsible partnerships.